Language teaching and the reproduction of anti-violence narratives: a critical discourse analysis - Khomarudin; Maimunah Mudjahid; Rokhmatul Ummah (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2026)
Indonesia, with its rich ethnic, cultural, and religious diversity, still faces social tensions that often appear in everyday language. These expressions may seem ordinary, yet they can carry harmful meanings and shape how people relate to one another. In this context, the national education system is expected to cultivate social sensitivity, empathy, and intercultural awareness as foundations for social cohesion. Language teaching, therefore, functions not merely as a linguistic practice but as a sociocultural and ideological space where values are produced, negotiated, and reproduced. This study examines how language teaching contributes to the reproduction of anti-violence narratives by promoting empathy, tolerance, and non-violence. The respondent of this research are 100 students and 10 lecturers of Tadris Bahasa Inggris and Bahasa Indonesia UIN Siber Syekh Nurjati Cirebon. Interview and observation are used to collect the data. Employing a qualitative field-based design, the study analyzes language teaching practices using Fairclough’s Critical Discourse Analysis, focusing on text, discursive practice, and sociocultural context. The findings reveal that language classrooms play a strategic role in both challenging normalized symbolic violence and reinforcing anti-violence values through everyday pedagogical discourse. Integrating ethical and intercultural values into language instruction is shown to contribute significantly to social cohesion and peace-building in Indonesia’s multicultural higher education context.